PROVIDING RADIO BROADCASTING SUBJECT FOR IMPROVING STUDENTS'S SPEAKING AND AS A NEW TREND WRITING SKILLS - Sumira Sumira (Universitas Negeri Padang, 2015)
Every educational institution requires its own characteristics to define its particular competence and skills of its graduates. By having the specification, the institution rviil help the students to find their best job. So that, it is important to provide the students rvith some subjects that can give them the practical experiences instead of provide them only with theoretical understanding. Therefore Politeknik Negeri Padang implements and adopts some specific subjects as a feature/ identity in its curriculum. The aim of this article is describing the competence and activities in Radio Broadcasting class which is a compulsory subject for students of English Department Politeknik Negeri Padang. Therefore, it may be used to improve students' speaking and writing skills. This article explores possible activities that are usually conducted by students when they are taking this subject to improve their productive skills (speaking and writing). In conducting the class. the teacher asks the students to make some writing task and broadcast it in radio studio. Hence the students can get the real environment to practice their productive skills.